Curcumin improves necrotising microscopic colitis and cell pyroptosis by activating SIRT1/NRF2 and inhibiting the TLR4 signalling pathway in newborn rats. Issue 7 (October 2020) - Yin, Yiyu; Wu, Xiaole; Peng, Bei; Zou, Huaxin; Li, Shixian; Wang, Jian; Cao, Junhua
This study aimed to explore comprehensively the biological function of curcumin, and its underlying mechanism, in protecting from necrotising microscopic colitis in newborn rats. A total of 20 normal healthy rats were selected, and a necrotising enterocolitis (NEC) model was established. After hypoxia and hypothermia stimulation, these rats were treated with different doses of curcumin (control group, NEC model group, NEC+20 mg/kg curcumin and NEC+50 mg/kg curcumin). Inflammation was identified using hematoxylin and eosin staining, and inflammatory factors were detected via ELISA. The mRNA and protein levels of SIRT1, NRF2, TLR4, NLRP3 and caspase-1 were determined by quantitative RT-PCR and Western blotting, respectively. Curcumin improved the inflammatory condition of NEC and inhibited the expression of inflammatory factors in NEC newborn rat intestinal tissue. Furthermore, the SIRT1/NRF2 pathway was inhibited in the intestinal tissue of NEC newborn rats, whereas curcumin treatment induced the activation of the SIRT1/NRF2 pathway and inhibited TLR4 expression in these animals. In addition, curcumin could also inhibit the expression of inflammatory factors and alleviate the LPS/ATP-induced focal death pathway in intestinal epithelial cells through the SIRT1 pathway. Curcumin can improve necrotising microscopic colitis and cell pyroptosis by attenuating NEC-induced inhibition of SIRT1/NRF2 and inhibiting the TLR4 signalling pathway in newborn rats.